A Prospective Study Comparing Two-Time Points of Thyroid Hormone Replacement during the Holy Month of Ramadan - Zeinab Dabbous; Buthaina Alowainati; Sara Darwish; Hamda Ali; Seleena Farook; Mariam Al Malaheem; Abeir Abdalrubb; Wajiha Gul; Wajiha Abu Haliqa (International Journal of Endocrinology)
Background. Muslims all over the world fast during the month of Ramadan from dawn until dusk. There is little data regarding the best timing of levothyroxine intake during the month of Ramadan where taking it on an empty stomach represents a challenge to most patients. Our study aims to compare two-time points of levothyroxine intake during Ramadan in terms of change in thyroid stimulating hormone (TSH), compliance, and convenience. Study Design and Methods. This was an open-label, randomized, prospective trial. Adult patients known to have primary hypothyroidism with stable TSH for the last 6 months who intended to fast during the month of Ramadan were invited to participate in this prospective study. The study took place during Ramadan of H1438 (May-June 2017). All patients were randomly assigned to two groups. In group A (n= 50) patients took levothyroxine 30 minutes before breaking the fast at sunset (iftar), and in group B (n= 46) patients took it 30 minutes before an early morning meal before sunrise (suhour). Results. TSH levels increased in both group A (from 1.99 to 3.28 mIU/L) and group B (from 1.54 to 3.28 mIU/L) after Ramadan fasting. There was no difference between the two groups. Compliance with intake instructions, all of the time, was reported in 41.6% of group A and 35.7% of group B patients. In both the groups, 95% of patients said it was convenient for them to take the medication at the assigned time. Conclusion. Choosing an optimal time for levothyroxine intake during the month of Ramadan remains a challenge. The current study did not provide any evidence on ideal time and dose of levothyroxine administration during fasting to manage hypothyroidism. Studies with a larger number of patients need to be done to further explore this issue.